2018
DOI: 10.31142/ijtsrd14595
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral Analysis, DFT and Antimicrobial of Some Novel Benzimidazole Derivatives

Abstract: Two novel 2-substituted benzimidazole derivatives were synthesized from 2-chloromethyl benzimidazole and 2-(2-chlorophenyl) imidazole with 1H-1,2,4-triazol-3-amine structures were characterized by Infrared spectroscopy, Nuclear magnetic resonance, (1H, 13C), Elemental analysis. Density functional theory (DFT) studies were performed using the B3LYP/6 31G (d, p) basis set to expand imminent into their structural properties. All the synthesized compounds were screened for antimicrobial activity against a panel of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The direct condensation of 2-(bromomethyl)-1 H -benzimidazole ( 1 ) with 2-aminothiazole was carried out to give the N -((1 H -benzimidazol-2-yl)methyl)thiazol-2-amine ( 2 ) [43],which underwent diazo coupling with different aryl diazonium chorides, yielding the corresponding N -((1 H -benzimidazol-2-yl)methyl)-5-(aryldiazenyl)thiazol-2-amines ( 3a – c ), as shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…The direct condensation of 2-(bromomethyl)-1 H -benzimidazole ( 1 ) with 2-aminothiazole was carried out to give the N -((1 H -benzimidazol-2-yl)methyl)thiazol-2-amine ( 2 ) [43],which underwent diazo coupling with different aryl diazonium chorides, yielding the corresponding N -((1 H -benzimidazol-2-yl)methyl)-5-(aryldiazenyl)thiazol-2-amines ( 3a – c ), as shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…The chemistry of benzimidazole moiety is of very high importance in the field of medicinal research ( Digwal et al, 2016 ; El-Feky et al, 2015 ; Evans et al, 2015 ; Mavrova et al, 2013 ; Hranjec et al, 2012 ; El-Gohary and Shaaban, 2014 , 2015 ; Mahalakshmi and Chidambaranathan, 2015 ; Nara et al, 1989 ; Kus et al, 2008 ). Several substituted benzimidazole derivatives ( Monforte et al, 2010 , 2009 ; Monforte et al, 2008 ) have been reported as potent HIV-1 inhibitors ( Fig.…”
Section: Introductionmentioning
confidence: 99%